2021
DOI: 10.15408/ijee.v8i2.21679
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Guessing Game in Improving the Speaking Skills of Elementary School Students

Abstract: Guessing game is a part of Communicative Language Teaching (CLT), which will create an atmosphere for students to increase the desire to learn languages. However, learning with games makes students undisciplined and requires a long time. This study aims to determine the effect of learning English using a guessing game method on the speaking skills of elementary school students. The study is a one-group pretest-posttest design implemented at the Islamic Elementary School in Yogyakarta. The study sample consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…It was proven by the results of their classroom action research in which out of 24 students, 15 of them (62.5%) reached the scores of 70 or higher in speaking tests in cycle 1, while in cycle 2, or after the teacher applied language games in their teaching, the number increased to 21 students (87.5%) who obtained the scores of 70 or higher (Marzuki & Kuliahana, 2021). Meiningsih and Madya found in their research that students' speaking skills aspects of vocabulary, pronunciation and fluency significantly improved after learning with guessing games (Madya & Meiningsih, 2021). Saha and Singh (2021) concluded in their research work that games developed students' speaking skill in which positive atmosphere of the classroom served them opportunities to speak (Saha & Singh, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…It was proven by the results of their classroom action research in which out of 24 students, 15 of them (62.5%) reached the scores of 70 or higher in speaking tests in cycle 1, while in cycle 2, or after the teacher applied language games in their teaching, the number increased to 21 students (87.5%) who obtained the scores of 70 or higher (Marzuki & Kuliahana, 2021). Meiningsih and Madya found in their research that students' speaking skills aspects of vocabulary, pronunciation and fluency significantly improved after learning with guessing games (Madya & Meiningsih, 2021). Saha and Singh (2021) concluded in their research work that games developed students' speaking skill in which positive atmosphere of the classroom served them opportunities to speak (Saha & Singh, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…The results of the study showed a significant increase in students' listening skills. A study conducted by (Meiningsih & Madya, 2021) found that whisper games were effective in improving the speaking skills of elementary school students who were learning English as a second language. In this study, students were tested using the whisper game technique in learning English.…”
Section: Introductionmentioning
confidence: 99%
“…Language games increase students' motivation (Lubis et al, 2021), allowing them to acquire theoretical abilities and use the language in daily activities (Casañpitarch, 2018). Several language games that can be used to improve students' speaking skills are available on various learning platforms (Madya & Meiningsih, 2021;Ritonga, Febriani et al, 2022;Adansia & Oringo, 2022). Word chain games can be used to improve students' English vocabulary (Maulani, 2021;Novi Rina Dewi & Alfany Fardan Syahuma, 2022;Bahang, 2022).…”
Section: Introductionmentioning
confidence: 99%